Pembinaan Lansia Melalui Terapi Menggambar dan Senam Otak dalam Pencegahan Demensia di UPT PSTW Banyuwangi - Daviyana, Yuldani Adinda; Intania, Tirsa; Fadilah, Shinta Nur; Nurhidayah, Ririn; Pagaksari, Faridatul Hikmah; Wulandari, Selvia; Susanto, Tantut (Poltekkes Kemenkes Aceh, 2025)
Cognitive function will decline with age, risk factors that can affect cognitive function decline are heredity from family, education level, brain injury, toxins, lack of physical activity, and chronic diseases such as Parkinson's, heart, and stroke. Implementation strategies to improve cognitive function in the elderly can be implemented with brain stimulation games as one of the knowledge-enhancing techniques that have been proven to be able to overcome memory disorders in the elderly. In this community service, the elderly are asked to draw according to their imagination after which the elderly take part in brain gymnastics guided by students which are then evaluated using the MMSE (Mini-Mental State Examination) questionnaire. By carrying out group activity therapy, it can improve cognitive function in the elderly so that it can prevent dementia in the elderly at UPT PSTW Banyuwangi